Flavors increase adolescents' willingness to try nicotine and cannabis vape products. (1st May 2023) - Chaffee, Benjamin W.; Couch, Elizabeth T.; Wilkinson, Monica L.; Donaldson, Candice D.; Cheng, Nancy F.; Ameli, Niloufar; Zhang, Xueying; Gansky, Stuart A.
Abstract: Background: Certain product characteristics, such as flavor, may increase adolescents' willingness to try vaped nicotine and cannabis (marijuana) products. Methods: A discrete choice experiment embedded within the 2021–2022 California Teens Nicotine and Tobacco Project Online Survey was administered to a non-probability sample of N = 2342 adolescents ages 12–17. Participants were sequentially presented four randomly-generated pairs of hypothetical vape products that varied in device type (disposable, refillable), content (nicotine, marijuana, "just vapor"), and flavor (seven options) and asked which of these (or neither) they would be more willing to try if a best friend offered. Conditional logistic regression quantified associations between product characteristics and participants' selections, including interactions by past 30-day use of e-cigarettes, marijuana, or both. Results: Candy/dessert, fruit, and fruit-ice combination flavors were all associated with greater willingness to try a vape product (versus tobacco flavor) among participants not using e-cigarettes or marijuana, those using only e-cigarettes, and those co-using e-cigarettes and marijuana. Among participants only using marijuana, the most preferred flavors were no flavor, candy/dessert, and icy/frost/menthol. Among participants not using e-cigarettes or marijuana, model-predicted willingness to try a displayed vape product was greater when products were sweet or fruit flavored than tobacco or unflavored, regardless of whether displayed options contained nicotine (fruit/sweet: 21 %, tobacco/unflavored: 4 %), marijuana (fruit/sweet: 18 %, tobacco/unflavored: 6 %), or "just vapor" (fruit/sweet: 29 %, tobacco/unflavored: 16 %). Conclusions: In this online non-probability sample, flavors in nicotine and cannabis vape products increased adolescents' willingness to try them. Comprehensive bans on flavored vapes would likely reduce adolescent use. Highlights: Adolescents were more willing to try flavored vapes than unflavored vapes. Flavors enhanced willingness for both nicotine and cannabis vape products. Flavors enhanced willingness among nicotine and cannabis users and non-users. Comprehensive bans on flavored vape products would likely reduce adolescent use.